GAMBARAN PERUBAHAN POSTUR TUBUH PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) AKIBAT PENGGUNAAN TAS PUNGGUNG BERAT - I Gusti Ayu Puja Astuti Dewi; Ida Ayu Putu Widyastuti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2016)
Background: The change on body posture could be caused by carrying a heavy backpack that disturb the development of the spine. If such condition continues, it could lead to an irreversible change on the posture. Aim: To identify the change on body posture of students of SMPN 7 Denpasar due to carrying heavy backpack. Methods: The study was a descriptive, observational, cross sectional study. There were 82 respondents involved in the study, which were selected through purposive sampling. The data were collected by using Adam Forward Bending Test checklist and analyzed descriptively. Results: It was found that majority of respondents (105; 37%) had unsymmetrical shoulder posture and generally 114 (40%) respondents had unsymmetrical body posture, in which 65 (54%) of them were male and 49 (30%) respondents were female. Conclusion: The change on students’ body posture could be prevented by providing education to students on how to use the backpack properly and suitable to their body capacity, conduct an examination on students’ body posture periodically, provide book lockers in schools and production of safe backpack for children. Subsequent research are necessary to be carried out to analyze the issue on organ dysfunction due to using heavy backpack. Keywords: backpack, body posture, students